Efficient and practical total synthesis of (+/-)-alpha-cuparenone - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthesis-Stuttgart, 2007)
A one-pot cyclopentannulation approach as the key step for the total synthesis of (+/-)-alpha-cuparenone is described.
Keywords: Alkylation; annulation; hydroboration-oxidation; reduction

Facile total synthesis of (+/-)-alpha-cuparenone employing diallylation and RCM as key steps - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
A short and concise total synthesis of alpha-cuparenone employing one-pot diallylation and RCM as the key steps is described. (c) 2006 Elsevier Ltd. All rights reserved.

Total synthesis of pulchellalactam via an RCM strategy - Chavan, Subhash P.; Pathak, Ashok B.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synthetic Communications, 2007)
Total synthesis of (Z) pulchellalactam, a CD protein tyrosine phosphatase inhibitor, from commercially available methallyl chloride employing ring-closure metathesis (RCM) as a key step is described.
Keywords: alkaloid; Natural products; pulchellalactam; RCM; Total synthesis

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction

Formal synthesis of (+/-)-camptothecin via tricyclic lactone as key synthon - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
Formal synthesis of (+/-)-camptothecin via CDE tricyclic lactone employing tandem Michael addition, Dieckmann condensation and addition-elimination reaction as key steps starting from glycinate is described. (C) 2010 Elsevier Ltd. All rights reserved.